CHENG HO MOSQUE AND SOCIAL STATUS : A STUDY ON THE EXISTANCE OF CHINESE MUSLIM WITHIN SOCIOCULTURAL RELATIONS IN SURABAYA, INDONESIA - Eva Putriya Hasanah; Moh. Ali Aziz; Sokhi Huda; Hepi Fauzi (Harmoni, 2022)
This article is a type of qualitative research using data collection techniques, namely documentation and interviews which discuss the impact of Cheng Ho Mosque for the sociocultural relations of Chinese Muslims with various parties in Indonesia. Before the construction of the Cheng Ho Mosque, being a Chinese Muslim in Indonesia was more difficult than being a Chinese. Chinese Muslims are like a minority within a minority and find very difficult to establish relationships with other non-Chinese Muslim groups in Indonesia. Likewise, his relationship with the Chinese ethnic group itself is very limited. This article finds, the presence of the Cheng Ho mosque has a new impact on the lives of Chinese Muslim today. The existence of Chinese Muslim has been widely known by the public. Both in social and cultural activities began to be widely known and understood. The relations with various parties are very good. The existence of Chinese Muslims can become a mediator in connecting and solve the problem among various parties like Nahdlatul Ulama, Muhammadiyah, academics, Chinese consulate general, non-Muslim Chinese communities, and other ethnic communities in Surabaya, East Java. Even indirectly have an impact on China’s public Diplomacy in Indonesia.